2006
DOI: 10.5271/sjweh.1015
|View full text |Cite
|
Sign up to set email alerts
|

Objective neuropsychological test performance of professional divers reporting a subjective complaint of “forgetfulness or loss of concentration”

Abstract: Objective This study attempted to determine whether the higher prevalence of reported "forgetfulness or loss of concentration" among professional divers can be confirmed using objective neuropsychological tests. Secondary aims were to qualify the functional nature of the complaints and to ascertain whether reduced performance was linked to diving history. MethodsIn a case-control study, the neuropsychological test performance of divers complaining of moderate or severe "forgetfulness or loss of concentration" … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…This supports the concept that the symptom is not entirely psychosomatic. Further, in a random sample selected from respondents from this study, we have found that the symptom was associated with poorer memory performance in objective neuropsychological testing [19] and reduced grey matter volume in brain areas associated with memory function in a preliminary magnetic resonance imaging analysis [20]. These differences, however, did not amount to abnormality.…”
Section: Discussionmentioning
confidence: 87%
“…This supports the concept that the symptom is not entirely psychosomatic. Further, in a random sample selected from respondents from this study, we have found that the symptom was associated with poorer memory performance in objective neuropsychological testing [19] and reduced grey matter volume in brain areas associated with memory function in a preliminary magnetic resonance imaging analysis [20]. These differences, however, did not amount to abnormality.…”
Section: Discussionmentioning
confidence: 87%
“…Neuropsychological testing methods have been described elsewhere [17] and are summarised here. The Logical Memory (LM) test, from the Wechsler Memory Scale III, and the California Verbal Learning Task (CVLT) II were used to measure immediate and delayed memory.…”
Section: Methodsmentioning
confidence: 99%
“…Current IQ measured using the Wechsler Abbreviated Scale of Intelligence (WASI) gave an estimate of global intellectual function (full score) and two sub-components of current intelligence: Matrix Reasoning (fluid intelligence) and Vocabulary (crystallized intelligence). The data gathered from this test battery were standardised ( z scores) and used to generate summary/composite scores reflecting memory performance (MemComp) and executive function (ExecComp) as described elsewhere [17]. Neuropsychological tests were always presented in the same order (CANTAB, CVLT, LM, WASI) using standardised instructions.…”
Section: Methodsmentioning
confidence: 99%
“…There is a real risk that the sample of respondents is not representative for British divers in general and that the impact on health related quality of life (HRQL) is underestimated [61,62]. Neuropsychological tests confirmed the cognitive complaints of the "forgetful" divers but other medical examinations were not included [63].…”
Section: Epidemiological Studiesmentioning
confidence: 99%